2007
DOI: 10.1300/j398v06n03_02
|View full text |Cite
|
Sign up to set email alerts
|

Clients' Perceptions of the Therapeutic Process

Abstract: Recently researchers in the family therapy field have encouraged a focus on aspects of therapy common across all models that are important to therapeutic change. The purpose of this study was to build on the "common factors" literature by exploring clients' perspectives of what was useful to their therapeutic experience. Quantitative and qualitative measures were used to collect data from 41 clients who participated in therapy at a university-based family therapy clinic. Quantitative results indicated that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 72 publications
0
16
1
Order By: Relevance
“…Clients’ pretherapy reflections can include a degree of hopefulness about their prospects for coming to therapy with convictions that their lives will be better by the end of treatment (Ward et al., 2007). They also can envision specific outcomes such as therapy helping them to create closer relationships or to making sense of things in their lives (Stanbridge, Burbach, Lucas, & Carter, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Clients’ pretherapy reflections can include a degree of hopefulness about their prospects for coming to therapy with convictions that their lives will be better by the end of treatment (Ward et al., 2007). They also can envision specific outcomes such as therapy helping them to create closer relationships or to making sense of things in their lives (Stanbridge, Burbach, Lucas, & Carter, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Once in therapy, clients reported the sessions to be a safe haven of comfort and hope where they could experience a respectful and relaxed atmosphere in which to converse (Allen & St. George, 2001; Newfield et al., 1990). Those clients expressing a positive experience with therapy had a tendency to use words such as supportive, unbiased, nonjudgmental, warmth, feeling accepted, engaged, context for change, collaborative, comfortable, caring, involvement, trust, and understanding (Howe, 1996; Odell, Butler, & Dielman, 2005; Schäfer, 2008; Singer, 2005; Smetana & Bigner, 2005; Smith, Yoshioka, & Winton, 1993; Stanbridge et al., 2003; Ward et al., 2007; Young & Cooper, 2008). Of critical importance to some clients was having a regularly scheduled session where they could (a) interact with each other differently, (b) limit the influence of their everyday problems (Bischoff & McBride, 1996; Ward et al., 2007; Wark, 1994b), and (c) focus on relationships (Bowman & Fine, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the act of seeking help from another, who is not a friend or acquaintance, can be quite an embarrassing experience for the client (Goldin & Bordan, 1999). In general, researchers have found that the therapeutic relationship between counsellor and client is the best predictor of a positive outcome (Smith, Thomas, & Jackson, 2004), and the most helpful aspect of clients' therapeutic experience (Ward, Linville, & Rosen, 2007).…”
Section: Relationship In Counsellingmentioning
confidence: 99%